Nanoporous Carbons: Looking Beyond Their Perception as Adsorbents, Catalyst Supports and Supercapacitors. Issue 1 (11th December 2015) - Bandosz, Teresa J.
Abstract: The discovery of carbon nanoforms, and especially graphene, has opened up new directions of science and technology. Many applications are based on the unique properties of graphene, such as its high electrical and thermal conductivity, strength, flexibility, photoactivity and transparency. Inspired by the emerging graphene science, we directed our efforts to the exploration of new applications of nanoporous (microporous) carbons. Their matrix is built of distorted graphene layers, between which pores with sizes ranging from a fraction of a nanometer to hundreds of nanometers exist. This is a very unique feature of nanoporous carbons resulting in their developed surface areas. Moreover, there are vast possibilities to modify the surface chemistry of carbons and thus their surface properties. Even though the traditional applications of porous carbons focus mainly on adsorption and separation, we decided to explore them as photocatalysts, oxygen reduction catalysts and sensors. Related to their visible‐light activity, their possible application in solar energy harvesting is also indicated. This Personal Account presents our paths leading to the exploration of these directions, describing the results collected and difficulties encountered, along with the challenges remaining to be addressed. Abstract : Nanoporous carbons are built of distorted graphene layers surrounding pores with sizes ranging from a fraction of a nanometer to hundreds of nanometers. This Personal Account provides the background and the history of our current approach to nanoporous carbons, with a focus on exploring the photoactivity of carbons in visible light and their electronic properties. In particular, the applications of nanoporous carbons as sensors, photocatalysts and solar‐cell components are discussed.